A Rapid Assessment of the Marine Megafauna Biodiversity Around South Bali, Indonesia - Mustika, Putu Liza Kusuma; Williams, Rob; Kadarisman, Hanggar Prasetio; Purba, Andri Oktapianus; Maharta, I Putu Ranu Fajar; Rahmadani, Deny; Faiqoh, Elok; Dewantama, I Made Iwan (Frontiers in Marine Science, 2021)
A low-cost, small-boat, rapid assessment survey was conducted on the waters off the southern Peninsula of Bali. The objectives were: (1) to conduct an inventory of cetacean species in the study area; (2) to map cetacean distribution to inform the design of the Badung MPA; (3) to estimate relative abundance of cetaceans and record information on presence and distribution of other marine megafauna; and (4) to train observers in the use of distance sampling methods. The survey adopted a “training while doing” approach to build local capacity for marine biodiversity monitoring, while collecting a snapshot of data to assess species richness and distribution. The survey accomplished its first two objectives, but due to violation of underlying assumptions, had mixed success with the third objective. Our survey revealed that the waters off the southern Peninsula of Bali support a rich cetacean fauna, with at least seven cetacean species, other marine megafauna, and avian species. Seven cetacean species found on our survey include: spinner dolphin (Stenella longirostris), pantropical spotted dolphin (Stenella attenuata), Fraser’s dolphin (Lagenodephis hosei), Risso’s dolphin (Grampus griseus), bottlenose dolphin (Tursiops sp.), Bryde’s whale (Balaenoptera edeni), and sperm whale (Physeter macrocephalus). Density estimates were low for all whales combined, but seem implausibly high for dolphins; likely due to violation of assumptions of distance sampling methods. Future surveys should include sufficient time for training to generate reliable abundance estimates. A dedicated bycatch study is needed to understand sustainability of bycatch mortality relative to reliable abundance estimates.